Learning for a new world. Report 2. Theme sustainable development / Elsi Brith Fodal - Brith Fodal, Elsi (2004)
Learning for a new world, the role of eduction, the world situation, forty language, one goal, would you like a little tuft, secret assignment for ecoschool, from nature study to sustainablel development.